Pengaruh Model Pembelajaran Matematika, Media Jaring-Jaring terhadap Kemampuan Pemecahan Masalah - Nurul Hikmah (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of this study was to determine the effect of constructive learning models on mathematics subjects, the benefits of net media on cube and beam material, students 'problem solving abilities on cube and beam material and the influence of constructive approaches and net media on students' problem solving abilities in cube and beam material in class VIII. The method used in this study is an experimental method that aims to determine the effect of each variable. This study also uses quantitative methods with statistical calculations to get the right and definite results. The results of data analysis using the t test are as follows tcount> t table ie (0.146> 5.25) then H0 is rejected. This means that there is the influence of constructive learning models and net media on students' mathematical problem solving abilities.